2012
DOI: 10.1002/qj.843
|View full text |Cite
|
Sign up to set email alerts
|

The structure and evolution of lower stratospheric frontal zones. Part 1: Examples in northwesterly and southwesterly flow

Abstract: The structure, evolution and dynamics of two lower stratospheric frontal zones are examined from a basic state variables perspective. The case studies highlight the asynchronous evolution of the lower stratospheric and upper tropospheric frontal portions of upper level jet-front (ULJF) systems, as well as some substantial differences in lower stratospheric frontal development that occur in southwesterly and northwesterly flow. The evolution of the ULJF in northwesterly flow was characterized by an initially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…This subsidence was responsible for vigorous tilting frontogenesis that extended from the tropopause down to nearly 700 hPa (Figure (b)). The weakening of what appears to be a rather robust lower stratospheric front by this subsidence is consistent with the findings of Lang and Martin () concerning lower stratospheric fronts in northwesterly flow. A wider, wave‐scale subsidence region was associated with curvature vorticity advection and, as at earlier times in this case, the gradient of subsidence was large on the cold side of the upper baroclinic zone (Figure (c)).…”
Section: Discussionsupporting
confidence: 91%
“…This subsidence was responsible for vigorous tilting frontogenesis that extended from the tropopause down to nearly 700 hPa (Figure (b)). The weakening of what appears to be a rather robust lower stratospheric front by this subsidence is consistent with the findings of Lang and Martin () concerning lower stratospheric fronts in northwesterly flow. A wider, wave‐scale subsidence region was associated with curvature vorticity advection and, as at earlier times in this case, the gradient of subsidence was large on the cold side of the upper baroclinic zone (Figure (c)).…”
Section: Discussionsupporting
confidence: 91%
“…Geographically, the climatological analysis suggested a preference for lower‐stratospheric fronts to occur over the Intermountain West: 133 (72%) of all 185 cases were identified in the Intermountain West and 52 (28%) of all 185 cases were identified in eastern North America. Motivated by the work of Lang and Martin (2012, 2013b), which suggested that there is a preference for lower‐stratospheric fronts to develop in southwesterly flow, the composite and case‐study analyses focused on the 54 (29%) lower‐stratospheric fronts that occurred in southwesterly flow. The southwesterly flow cases were further partitioned into geographical location before compositing.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…While the upper‐tropospheric front is often highlighted as the main dynamical structure in a tropopause jet–front system, the analyses of Lang and Martin (2012, 2013b) emphasized the fact that via the thermal wind relationship, frontal development can also occur in the lower‐stratospheric vertical shear zone above a tropopause jet streak (i.e. ‘the region of the jet stream axis with the greatest winds’; American Meteorological Society, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations